2020
DOI: 10.7717/peerj.8875
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural differences in perception of trees described by parents bringing up children in Warsaw and Jedlińsk, Poland

Abstract: Parents’ attitudes to trees and nature are reflected not only in their children’s outdoor activity, but also in the way they perceive, learn and value the environment. One hundred and eleven respondents, divided into two groups by place of residence, assessed statements in a survey questionnaire. Two groups of questions aimed at evaluating tree benefits and disservices as perceived by urban and rural parents, and identifying their preferences concerning outdoor activity of their children. Tree benefits and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
2
2
0
Order By: Relevance
“…What is particularly interesting, almost one-fifth of the respondents revealed that they were in the parks daily, and almost one third were in the parks several times a week. This result proves that benefits of nature (also shown in other studies ( Corazon et al, 2019 ; Suchocka, Jankowski & Błaszczyk, 2019 )), and their need to be surrounded by the natural environment ( Wojnowska-Heciak, 2019 ; Wojnowska-Heciak et al, 2020 ). This trend can also be seen among the residents of other countries; in Denmark, 43 per cent of the respondents reported visiting green spaces every day and 91 per cent at least once a week ( Schipperijn et al, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…What is particularly interesting, almost one-fifth of the respondents revealed that they were in the parks daily, and almost one third were in the parks several times a week. This result proves that benefits of nature (also shown in other studies ( Corazon et al, 2019 ; Suchocka, Jankowski & Błaszczyk, 2019 )), and their need to be surrounded by the natural environment ( Wojnowska-Heciak, 2019 ; Wojnowska-Heciak et al, 2020 ). This trend can also be seen among the residents of other countries; in Denmark, 43 per cent of the respondents reported visiting green spaces every day and 91 per cent at least once a week ( Schipperijn et al, 2010 ).…”
Section: Discussionsupporting
confidence: 85%
“…Too slippery, uneven or sand and gravel paths were indicated as one of the main barriers in parks. This finding is quite surprising for the authors who, while actively working in the design field, preferred stabilized sand and gravel surfaces in green areas as nature-friendly and water-permeable [ 24 , 76 , 77 , 78 ]. This pavement surface characteristic is not covered in the guidelines of universal design though this should serve as a direction in reconciling the needs of all users [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of open space offers a variety of economic, environmental and social function values [ 13 , 14 , 15 , 16 ] that provide important space-filling elements in the form and layout of cities [ 17 , 18 , 19 ]. The potential impacts of urban parks on public health have long been recognized in the literature [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is particularly interesting, almost one-fifth of the respondents revealed that they were in the parks daily, and almost one third were in the parks several times a week. This result proves that benefits of nature (also shown in other studies (Corazon et al, 2019;Suchocka, Jankowski & Błaszczyk, 2019)), and their need to be surrounded by the natural environment (Wojnowska-Heciak, 2019;Wojnowska-Heciak et al, 2020). This trend can also be seen among the residents of other countries; in Denmark, 43 per cent of the respondents reported visiting green spaces every day and 91 per cent at least once a week (Schipperijn et al, 2010).…”
Section: Discussionsupporting
confidence: 81%